“The message hurts, but it would be worse if nothing was said” – Communicating severe illness and the imminence of death to patients with end stage heart failure and their families – A longitudinal interview study - Annika Pohl; Maria Liljeroos; Tiny Jaarsma (PLoS ONE, 2025)
Aims Discussions about severe illness and the coming death do not often take place with patients with heart failure and their family. We therefore aimed to investigate how patients with end-stage heart failure and their family who discussed terminal illness and the imminence of death with a physician, experienced such communication, how they handled life emotionally and practically after said discussions, and if/how this changed over time. Methods A longitudinal interview study. Ten patients with end-stage heart failure and their closest kin were visited by a physician at home and discussed terminal illness during one visit and the imminence of death during another visit. They were interviewed three times about how they experienced the communication and how they handled life in this situation and in relation to the discussions. The interviews were analysed using qualitative thematic analysis by Braun and Clarke. Findings Two main themes and five subthemes were found. The first theme was ‘an honest and clear message hurts, but it would be worse if nothing was said’, and the subthemes included information on the experiences of communication, the desired level of communication by patients and family members and factors facilitating communication. The second theme was ‘A clear message helps in handling life’ with the subthemes of coping psychologically and practically. The findings indicate that for some patients and family members it was hard to have discussions about end-stage heart failure and the imminence of death. However, they found the discussions important and were happy that the information was not withheld from them. The discussions helped in handling life and most patients and family seemed to have found a way to accept and handle the situation. Practical planning often did not start until they heard from the physician that death could come soon. Conclusion This study confirms that patients and family members want and appreciate discussions about severe illness and the imminence of death and find them important. This can encourage physicians to change behaviour and engage in honest discussions, and to educate and train colleagues to do the same.